"I am not a theorist, I am an inspirer"*: How Nemirovich-Danchenko interpreted the Stanislavski system. Issue 1 (2nd January 2017) - Autant-Mathieu, Marie-Christine
Abstract: Conficts between the two leaders of the Moscow Art Theater: Stanislavski and Nemirovich-Danchenko, had repercussions in their way of directing. We will show how Nemirovich assimilates the basics of the Stanislavsky's system in the 1910s and how he transforms and adapts them when he directs performances in the 1930s. We will study the evolution of the terminology (subtext, atmosphere, creative state, interior monologue, kernel etc.) in his work on Anna Karenina (1937) and The Three Sisters (1940). This paper aims to present a variation in the Stanislavski system, produced not by one of his disciples but by a peer, a director who was originally a playwright and we intend to show how this literary background has an impact on Nemirovich's interpretation of the Stanislavski system.